Tinjauan Penangkalan Warga Negara Asing Dalam Peningkatan PNBP Negara Melalui Bidang Keimigrasian - Nugroho, Fauzan Afriansyah; Wiraputra, Anindito Rizki; Aji, Koesmoyo Ponco (Fakultas Syariah INSURI Ponorogo, 2022)
As a state of law, in carrying out state life, of course, it must always be based on the basis of law. The same applies to financial management, particularly to the management of state revenue sources, both through taxes and non-taxes. The high number of needs for money due to the current economic paralysis in Indonesia has encouraged several sectors to be able to contribute to the recovery of the economic paralysis. Immigration has a role in providing income for the state through the Non-Tax State Revenue (PNBP) sector, which is obtained through immigration services, both for Indonesian citizens and foreign citizens. In order to support an increase in income through the economic sector, especially through Non-Tax State Revenue (PNBP), an innovation is needed that can increase income for the Indonesian state. One of them is through prevention and deterrence for foreigners. Regulations regarding prevention and deterrence are contained in Article 91 of Law Number 6 of 2011 concerning Immigration. The high number of violations related to immigration regulations that occur today can be used by the Immigration Office in terms of increasing Non-Tax State Revenue, this is done for the sake of the stability of the country's economy for the sustainability of the welfare of the Indonesian people. As a developing country, Indonesia continues to strive in terms of increasing economic development. This is useful for improving the country's economy. In this case, a consistent government role is needed regarding increasing economic growth. Namely by issuing laws and regulations that can take advantage of violations of immigration regulations to become income for the state